ALS phenotype is influenced by age, sex, and genetics: A population-based study. (25th February 2020) - Chiò, Adriano; Moglia, Cristina; Canosa, Antonio; Manera, Umberto; D'Ovidio, Fabrizio; Vasta, Rosario; Grassano, Maurizio; Brunetti, Maura; Barberis, Marco; Corrado, Lucia; D'Alfonso, Sandra; Iazzolino, Barbara; et al.
Abstract : Objective: To assess the determinants of amyotrophic lateral sclerosis (ALS) phenotypes in a population-based cohort. Methods: The study population included 2, 839 patients with ALS diagnosed in Piemonte, Italy (1995–2015). Patients were classified according to motor (classic, bulbar, flail arm, flail leg, predominantly upper motor neuron [PUMN], respiratory) and cognitive phenotypes (normal, ALS with cognitive impairment [ALSci], ALS with behavioral impairment [ALSbi], ALSci and ALSbi combined [ALScbi], ALS–frontotemporal dementia [FTD]). Binary logistic regression analysis was adjusted for sex, age, and genetics. Results: Bulbar phenotype correlated with older age ( p < 0.0001), women were more affected than men at increasing age ( p < 0.0001), classic with younger age ( p = 0.029), men were more affected than women at increasing age ( p < 0.0001), PUMN with younger age ( p < 0.0001), flail arm with male sex ( p < 0.0001) and younger age ( p = 0.04), flail leg with male sex with increasing age ( p = 0.008), and respiratory with male sex ( p < 0.0001). C9orf72 expansions correlated with bulbar phenotype ( p < 0.0001), and were less frequent in PUMN ( p = 0.041); SOD1 mutations correlated with flail leg phenotype ( p < 0.0001), and were less frequent in bulbar ( p < 0.0001). ALS-FTD correlated with C9orf72 ( p < 0.0001) and bulbar phenotype ( p = 0.008), ALScbi with PUMN ( p = 0.014), and ALSci with older age ( p = 0.008). Conclusions: Our data suggest that the spatial–temporal combination of motor and cognitive events leading to the onset and progression of ALS is characterized by a differential susceptibility to the pathologic process of motor and prefrontal cortices and lower motor neurons, and is influenced by age, sex, and gene variants. The identification of those factors that regulate ALS phenotype will allow us to reclassify patients into pathologically homogenous subgroups, responsive to targeted personalized therapies.